Infection of human induced pluripotent stem cells by an oncogenic herpesvirus - Fan, Jiaojiao; Lin, Zhen; Zhang, Huiliang; Dai, Lu; Qin, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveAs one of the major human oncogenic viruses, Kaposi’s Sarcoma-associated Herpesvirus (KSHV) is closely related to several cancers such as Kaposi’s sarcoma (KS) and primary effusion lymphoma (PEL). KSHV can infect a broad tropism of human primary cells in vitro and in vivo. Embryonic stem cell-like pluripotent stem cells can be generated by the simultaneous introduction of several factors, into somatic cells, yielding induced pluripotent stem (iPS) cells. However, it remains unclear whether human induced pluripotent stem cells (hiPSCs) are permissive to KSHV and how this oncogenic virus infection may affect cellular gene profile.MethodsIn the current study, we examined whether hiPSCs were permissive to KSHV infection. The flow cytometry was used to assess the impacts of KSHV infection on hiPSCs viability and apoptosis. The Illumina RNA-Sequencing was used to determine cellular gene profile changed in KSHV-infected hiPSCs and lytically induced cells.ResultsWe report that KSHV successfully establishes latent infection in hiPSCs, which can be completely induced to lytic reactivation and release infectious virions. KSHV de novo infection arrests the growth of hiPSCs through inducing cell apoptosis. Transcriptomic analysis revealed significant changes in global cellular gene expression in KSHV-infected hiPSCs as well as lytically induced cells.ConclusionOur findings demonstrate hiPSCs as a powerful tool to explore the potential impacts of KSHV infection on stem cell functions and virus pathogenesis in stem cell differentiated cells.